Association between forced expiratory volume in 1 s and relapse-free survival in operable non-small cell lung cancer: a prospective cohort study with propensity score overlap weighting - Jing Cheng; Yang Du; Karl Sylvester; Shaoping Wu; Suixin Liu; Yaoshan Dun; Baiyang You; Siqian Fu; Ning Xu; Jeffrey William Ripley-Gonzalez; Ni Cui (BMJ Open)
Objectives Investigate the correlation between the percentage of predicted forced expiratory volume in 1 s (FEV1%pred) and survival outcomes, namely relapse-free survival (RFS) and overall survival (OS), in patients diagnosed with operable early-stage non-small cell lung cancer (NSCLC).Design Prospective observational study.Setting Clinical settings in Xiangya Hospital, Central South University, Hunan, China.Participants From November 2014 to December 2019, 775 operable patients with NSCLC, median age 58 years (IQR 13) with 40.6% women, were consecutively enrolled and underwent preoperative FEV1 assessment. All participants were evaluated using the FEV1%pred assessment. Subsequent treatments and operative interventions followed established protocols for NSCLC.Results During the follow-up, which lasted a median of 40 months (range 1–85 months) and continued until December 2021, 202 patients either relapsed or died. Optimal FEV1%pred cut-off was identified using receiver operating characteristic analysis. Results revealed 110 and 71 relapses and deaths per 1000 person-years for patients with FEV1 values of <82%pred and ≥82%pred, respectively. Cox proportional hazards models, adjusted for demographics, medical history and surgery characteristics with propensity score overlap weighting, revealed the significant impact of lower FEV1%pred on decreased RFS and OS. An FEV1%pred less than 82% displayed a significant association with decreased RFS (weighted HR, 1.55; 95% CI, 1.14 to 2.09; p=0.007) and OS (weighted HR, 1.50; 95% CI, 1.01 to 2.23; p=0.04).Conclusions Lower FEV1%pred values notably correlate with compromised RFS and OS in individuals operable for early-stage NSCLC, suggesting that FEV1%pred may serve as a valuable tool in evaluating and managing long-term recurrence risk in patients with early-stage NSCLC.Trial registration number ChiCTR2100048120.